Inflammatory-Related P62 Triggers Malignant Transformation of Mesenchymal Stem Cells through the Cascade of CUDR-CTCF-IGFII-RAS Signaling - Xiaoru Xin; Chen Wang; Zhuojia Lin; Jie Xu; Yanan Lu; Qiuyu Meng; Xiaonan Li; Yuxin Yang; Qidi Zheng; Xin Gui; Tianming Li; Hu Pu; et al. (Elsevier, 2018)
Inflammatory and autophagy-related gene P62 is highly expressed in most human tumor tissues. Herein, we demonstrate that P62 promotes human mesenchymal stem cells' malignant transformation via the cascade of P62-tumor necrosis factor alpha (TNF-α)-CUDR-CTCF-insulin growth factor II (IGFII)-H-Ras signaling. Mechanistically, we reveal P62 enhances IGFII transcriptional activity through forming IGFII promoter-enhancer chromatin loop and increasing METTL3 occupancy on IGFII 3' UTR and enhances H-Ras overexpression by harboring inflammation-related factors, e.g., TNFR1, CLYD, EGR1, NFκB, TLR4, and PPARγ. Furthermore, the P62 cooperates with TNF-α to promote malignant transformation of mesenchymal stem cells. These findings, for the first time, provide insight into the positive role that P62 plays in malignant transformation of mesenchymal stem cells and reveal a novel link between P62 and the inflammation factors in mesenchymal stem cells.